Nucleoside and Nucleotide Reverse Transcriptase Inhibitors Induce Aging by Inhibiting Telomerase Function - Shweta, Singh; Bechan, Sharma; Nikhat, Jamal Siddiqi (Journal of Clinical Research In HIV AIDS And Prevention, 2019)
The telomeres existing at the end of the eukaryotic chromosome, play an important role in localization, pairing of homologous chromosomes during cell division and synapsis formation, while telomerase is involved in maintenance of the telomere length. The application of antiHIV-1 molecules particularly NRTIs have been shown to interfere with telomerase function thereby inducing aging processes. Since the application of these molecules has already indicated production of oxidative stress and toxicity in AIDS patients, their adverse impact on telomerase function may further worsen the situation. In addition, the negative influence of antiHIV-1 regimens on certain host factors involved in telomerase function may enhance aging. HAART changes the landscape of the disease by progressively decreasing the progression of HIV-1, but exerts prolonged adverse effects on the telomerase function. Though there is no exact information available on this issue, intensive efforts are needed to explore regulation of telomerase expression in HIV infected individuals and particularly those receiving antiretrovirals.
Keywords: HIV; telomerase; Highly active antiretroviral therapy (HAART); telomere shortening; Nucleotide reverse transcriptase inhibitors; mitochondrial toxicity